Análise comparativa dos efeitos renais causados pelos contrastes de alta osmolalidade, baixa osmolalidade e isosmolar: papel do KIM-1 como detector precoce de injúria renal - Lima, Erika Gondim Gurgel Ramalho (2016)
Iodinated contrast media have been used in the last 60 years and are indispensable in medical practice. Among the complications arising from the use of contrast media, is contrast-induced nephropathy (CIN), which is the third most common cause of acquired renal failure and is associated with high mortality and morbidity. The aim of the study was to compare the renal effects of high-osmolar, low-osmolar and iso-osmolar contrast media; to verify the role of KIM- 1 as an early predictor of CIN; and evaluate the effect of contrast media on LLC-MK2 renal tubular cells. The experiments were performed in Wistar rats, with three types of contrast, at two doses and times of 24, 48 and 72 hours. Then, biochemical analyses of classical biomarkers and urinary KIM-1 were carried out, in addition to histological analysis. The project was approved by the Ethics Committee on Animal Research (CEPA) of the Federal University of Ceará (UFC), under protocol number 33/2015. In the in vitro study, LLC-MK2 renal tubular cells were used for evaluation of type of induced cell death by means of flow cytometry. When evaluating the groups treated with three different osmolar contrasts, a significant increase in plasma creatinine levels and reduction in glomerular filtration rate in the group receiving high- osmolar contrast were observed. Increased urinary KIM-1 expression and albuminuria were also found in the high-osmolar and iso-osmolar contrast groups. In the analysis of two doses with high-osmolar contrast, only the higher dose showed biomarker changes. In the analysis of times and high-osmolar contrast, classical biomarkers changed after 48 hours and, in the analysis of KIM-1, urinary expression was already identified at 24 hours. Apoptosis was detected in the analyzed contrast during in vitro assays in renal cells. Histological analysis showed moderate tubular change in the 48-hour group, with slight modifications in the other groups. In conclusion, we suggest that the high-osmolar contrast is more nephrotoxic than low- osmolar and iso-osmolar contrast media. Dose reduction suggests greater safety and KIM-1 showed superiority compared to classic biomarkers for early diagnosis of CIN.